Tense-aspect, transitivity and causativity : essays in honour of Vladimir Nedjalkov - Abraham, Werner; Kulikov, L. I.; Nedi͡alkov, V. P. (Vladimir Petrovich) (Studies in language companion series, 1999)
This collection presents typological work on tense, aspect, and epistemic modality in a variety of languages and against the background of different schools of thinking, among which the St. Petersburg Typological School developed and so masterfully implemented by the Petersburg linguist, Vladimir Petrovich Nedjalkov. The volume honors this reputed scholar for his life work. It is in mainly this spirit (and the EUROTYPE spirit) that the following scholars have contributed to the volume: T. Tsunoda on Warrungu (Australian indigeneous language), L. Kulikov on Vedic, K. Kiryu on Japanese, Korean an.